Neighborhood differences in patterns of syringe access, use, and discard among injection drug users: implications for HIV outreach and prevention education. - Buchanan, David; Shaw, Susan; Teng, Wei; Hiser, Poppy; Singer, Merrill (Journal of urban health : bulletin of the New York Academy of Medicine, 2003)
The article presents results from the Syringe Access, Use, and Discard: Context in AIDS Risk research project comparing two neighborhoods by (1) socioeconomic and demographic characteristics; (2) patterns of syringe access, use, and discard; and (3) encounters with a local human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS) outreach project targeted to injection drug users (IDUs). The results show that IDUs in more economically advantaged neighborhoods were more likely to acquire syringes from a single source (rather than multiple sources), more likely to inject alone in their own residence (rather than public injection locales), and more likely to dispose of syringes in private garbage cans rather alleys or dumpsters. These results are further associated with the likelihood of encountering street outreach workers, with IDUs in more affluent neighborhoods much less likely to have any such contacts. Based on the different patterns of access, use, and discard evident in each neighborhood, the results indicate that different and more carefully tailored local outreach and prevention strategies are urgently needed.
Keywords: Adolescent; Adult; Anthropology, Cultural; Child; Child, Preschool; Community-Institutional Relations; Connecticut; HIV Infections; Humans; Infant; Infant, Newborn; Interviews as Topic; Massachusetts; Middle Aged; Mobile Health Units; Needle Sharing; Pharmacies; Residence Characteristics; Socioeconomic Factors; Substance Abuse, Intravenous; Syringes